2004
DOI: 10.1152/ajpregu.00456.2003
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod differentially modulates photic and nonphotic phase response curves of hamsters

Abstract: Circadian pacemakers respond to light pulses with phase adjustments that allow for daily synchronization to 24-h light-dark cycles. In Syrian hamsters, Mesocricetus auratus, light-induced phase shifts are larger after entrainment to short daylengths (e.g., 10 h light:14 h dark) vs. long daylengths (e.g., 14 h light:10 h dark). The present study assessed whether photoperiodic modulation of phase resetting magnitude extends to nonphotic perturbations of the circadian rhythm and, if so, whether the relationship p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
38
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 43 publications
6
38
0
Order By: Relevance
“…However, photic and nonphotic effects on the clock can be dissociated. As discussed earlier, the magnitude of phase shifts to light is affected by prior photoperiod (shifts are smaller following exposure to long vs. short days), but the magnitude of activity-induced shifts has recently been shown to be unrelated to photoperiod (Evans et a/., 2004). The results of the present study now demonstrate the converse; a manipulation that can strongly potentiate nonphotic shifts does not affect a light input pathway to the clock.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, photic and nonphotic effects on the clock can be dissociated. As discussed earlier, the magnitude of phase shifts to light is affected by prior photoperiod (shifts are smaller following exposure to long vs. short days), but the magnitude of activity-induced shifts has recently been shown to be unrelated to photoperiod (Evans et a/., 2004). The results of the present study now demonstrate the converse; a manipulation that can strongly potentiate nonphotic shifts does not affect a light input pathway to the clock.…”
Section: Discussionsupporting
confidence: 73%
“…It is conceivable, for example, that the phase resetting effect of NMDA was in some way down-regulated as a result of exposure to LL so as to precisely offset the functional consequences of decreased amplitude. In fact, increased photoperiod has been shown to attenuate photic resetting in nocturnals (Evans, et al, 2004). Their results showed that light-induced phase shifts are larger in hamsters housed in LD 10:14 vs. 14:lO.…”
Section: Discussionmentioning
confidence: 96%
“…After approximately 1 mo in a short photoperiod, nocturnal rodents shift more in response to a light pulse during the early night than rodents exposed to long days (51,53). The isolated SCN of animals exposed to short days show a narrower peak of daily multiunit activity and, like the behavior, a larger phase shift following stimulation (54).…”
Section: Discussionmentioning
confidence: 96%
“…For example, diurnal sparrows exposed to 36 or 48 h of light before an 8-h advance or delay in their light cycle entrained more rapidly than birds subjected to darkness during the same interval (46). A number of agents including triazolam, Sildenafil, adrenalectomy, scheduled activity during usual rest, and dim light at night have been indicated to accelerate entrainment (47)(48)(49)(50)(51)(52). We propose that paradigms such as these may transiently reduce synchrony among SCN neurons or perhaps other circadian oscillators and, thus, speed entrainment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, activity-induced phase shifts associated with novel running wheels are caused by suppression of Period gene expression in the SCN of wild-type (WT) hamsters during subjective day (Maywood et al, 1999). Furthermore, the magnitude of phase shifts in response to photic stimuli is dependent on photoperiod, whereas that of nonphotic phase shifts is not (Evans et al, 2004). The tau mutation has been reported to increase the amplitude of nonphotic responses (Mrosovsky, et al, 1992; Biello and Mrosovsky, 1996).…”
mentioning
confidence: 99%